Proposal of the Functional System for the Airline Companies Financial Situation Assessment - Stopka, Ondrej; Bartuska, Ladislav; Caban, Jacek; Kapustina, Larisa M. (Communications - Scientific letters of the University of Zilina, 2019)
This paper presents the draft methodology to be applied for evaluating the financial health of airlines. In the introductory part, specific attributes, regarding the individual types of airlines, are described. Subsequent parts of the manuscript outline advantages and disadvantages to measure airlines performance when implementing financial indicators, as well as a general procedure to evaluate the financial situation of a company operating in the aviation industry. The most important part of the paper includes the proposal of the specific functional system to evaluate the economic performance of airlines. Financial evaluation itself (evaluation of financial indicators of the enterprise‘s economic performance) is performed through a particular case study when comparing several existing airlines.